The Septuagint of Jeremiah: a study in translation technique and recensions - Tucker, Miika (De Septuaginta investigationes, 2022)
Miika Tucker comprises a translation technical study of the Septuagint version of Jeremiah for the purpose of characterizing the translation. The conclusions draw from different types of changes that occur between chapters 1–28 (Jer a’) and 29–52 (Jer b’). Certain differences between the two reflect the revisional characteristics of the kaige tradition, which suggests that they were produced by a reviser who was invested in a revisionary tradition similar to kaige. Other differences constitute a change toward more natural Greek expression, which is the opposite of what one would expect from a revision since Greek idiom usually does not correspond to the formal characteristics of Hebrew. Such differences are to be understood to reflect a change toward more intuitive use of the Greek language by the first translator. Changes toward less formal equivalence of the Hebrew and the growth of the Hebrew text after the initial translation combined to form conducive conditions for revision.